Faktor Risiko Kejadian Hipertensi pada Ibu Hamil - Wiranto, Wiranto; Putriningtyas, Natalia Desy (Indonesian Journal of Public Health and Nutrition, 2021)
Background: Semarang City 2020, 1.36% of pregnant women with hypertension, in January 2021 there were 5.65% of pregnant women with hypertension, and 13.8% of cases were at Puskesmas Gunungpati. The purpose of the study was to analyze the risk factors for hypertension in pregnant women in the Puskesmas Gunungpati, Semarang City. Methods: The research method used was analytic observational research with a case control approach. The study was conducted in June-August 2021 at Puskesmas Gunungpati Working Area. The sampling technique used was quota sampling with a total sample of 74 respondents, with a comparison of case and control groups of 1: 1. The data analysis carried out was univariate analysis, bivariate analysis (Chi square test) and multivariate analysis (logistic regression test). Results: The p-value on the variables of pre-pregnancy weight was 0.008 (<0.05), sodium intake 0.005 (<0.05), potassium intake 0.465 (>0.05), calcium intake 0.005 (<0.05), gravidity 0.580 (>0.05), maternal age 0.021 (<0.05), and family history of hypertension 0.000 (<0.05). Conclusion: There is a relationship between pre-pregnancy weight, sodium intake, calcium intake, maternal age, and family history of hypertension with the incidence of hypertension in pregnant women. There is no relationship between potassium intake and gravidity with the incidence of hypertension in pregnant women.